Succession Process for Sustainability of Family Dairy Farming - Achmad Firman; Andre Rivianda Daud; Hasni Arief (Universitas Muhammadiyah Yogyakarta, 2023)
Succession is crucial in the small-scale dairy cattle business, predominantly managed by family members. The process of preparing a successor in a dairy farming family is a challenging endeavor. This study aims to explore the succession process through family business participation, the factors influencing a successor's participation, and succession patterns in family dairy farming. This study employed a quantitative method for multiple regression model and a qualitative method to compile the opinion of the succession patterns. The results revealed the low successor participation index for family business due to restricted time. Six variables significantly influenced successors’ participation in family dairy farms: family size, gender, employment status, number of dairy cattle, age, and farm size. The study’s findings generated two succession patterns: farm transfer and farm handover. The succession patterns preserved the existence of family dairy farms in Pangalengan District, West Java, Indonesia. Therefore, this study suggests to encourage the participation of potential successors to ensure the sustainability of family dairy farming.